Blockchain blueprint for a new economy - Swan, Melanie (O'Reilly Media, 2015)
Bitcoin is starting to come into its own as a digital currency, but the blockchain technology behind it could prove to be much more significant. Author Melanie Swan, Founder of the Institute for Blockchain Studies, explains that the blockchain is essentially a public ledger with potential as a worldwide, decentralized record for the registration, inventory, and transfer of all assets--not just finances, but property and intangible assets such as votes, software, health data, and ideas.